High-temperature-resistant copper-clad plate based on modified bismaleimide resin and preparation method of high-temperature-resistant copper-clad plate
By modifying the bismaleimide resin, adding hyperbranched polysiloxane and cyano-containing benzooxane, the problems of insufficient brittleness, dielectric properties and fiber adhesion of the resin are solved, and the preparation of high-performance copper clad plate is realized.
Patent Information
- Application Number
- CN202510115875.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-01-24
AI Technical Summary
Bismaleimide resin has disadvantages in terms of high molding temperature, high cured product brittleness, insufficient dielectric properties and fiber adhesion, which limits its application in the field of copper clad plates.
Modified bismaleimide resin by blending copolymerization reaction, and adding hyperbranched polysiloxane and cyano-containing benzooxazine to improve the glass transition temperature, fracture toughness and fiber adhesion of the resin.
It significantly improves the fracture toughness and heat resistance of the resin, reduces the dielectric constant and dielectric loss, improves the bonding ability to fibers, and meets the needs of high-performance copper clad plates.
Smart Images

Figure CN119871952A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation technology of a material for a high-temperature resistant copper-clad laminate, and in particular to a high-temperature resistant copper-clad laminate based on a modified bismaleimide resin and a preparation method thereof. Background Art
[0002] Printed circuit boards (PCBs) play a key role in connecting and supporting electronic devices. With the vigorous development of 5G technology, the performance requirements for printed circuit board substrate materials are also increasing. In the field of electronics and electrical, the application range of printed circuit board substrate materials is extremely wide. Copper clad laminate is the mainstream basic material for manufacturing PCBs. It is mainly composed of three major materials: resin, copper foil and glass fiber cloth. The overall performance of copper clad laminate depends to a large extent on the performance of the copper clad laminate resin matrix. At present, the matrix resins commonly used in substrate materials mainly include epoxy resins and phenolic resins. However, these resin materials are mainly suitable for the production of ordinary circuit boards. With the rapid development of electronic information technology, electronic products are further developing towards miniaturization, lightweight and high-density assembly. Their high dielectric constant and insufficient heat resistance restrict their application.
[0003] In recent years, bismaleimide resin (BMI) has become an ideal resin for copper clad laminate resin matrix due to its good heat resistance, dielectric properties, outstanding weather resistance, chemical resistance, etc. However, its mechanical properties, molding process, dielectric properties and poor adhesion on fibers have limited its direct application. Therefore, it is very necessary to modify bismaleimide resin. Developing high-performance resins with excellent comprehensive properties through modification is of great significance for expanding its application in the field of copper clad laminates. Summary of the invention
[0004] BMI has disadvantages such as high molding temperature and high brittleness of the cured product. Among them, high brittleness is the key obstacle to the development and application of BMI. At the same time, the dielectric properties of BMI and its adhesion to fibers need to be further improved.
[0005] In order to solve the above technical problems, the specific technical scheme of the high temperature resistant copper clad laminate based on modified bismaleimide resin and the preparation method of the present invention is as follows:
[0006] 1. A method for preparing a high temperature resistant copper clad laminate based on modified bismaleimide resin, characterized in that it comprises the following steps:
[0007] Step 1: Add three solids, namely, bismaleimide, cyano-containing benzoxazine BA-Ph, and hyperbranched polysiloxane, and a solvent into a reaction bottle, heat to a set temperature, and stir until the solution is uniform and transparent; the mass ratio of the total mass of the three solids to the solvent liquid is 15-70%, the amount of BA-Ph is 5-40% of the mass of bismaleimide, and the amount of hyperbranched polysiloxane is 5-20% of the mass of bismaleimide; the solvent includes one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, and dioxane, and the bismaleimide includes N,N"-(4,4"-methylenediphenyl)bismaleimide (BDM), BMI-70, and BMI-80.
[0008] Step 2: react the transparent solution obtained in step 1 at 120° C. for 3 hours to obtain a glue solution;
[0009] Step 3: Apply the glue prepared in step 2 evenly on the glass fiber cloth, and hang the fiber cloth to drip out the excess glue;
[0010] Step 4: Repeat the process of step 3 to obtain 8 pieces of glass fiber cloth soaked with glue;
[0011] Step 5: Put the 8 pieces of glass fiber cloth soaked with glue obtained in step 4 into an oven to dry the solvent at a set temperature to obtain 8 pieces of prepreg;
[0012] Step 6: stack the prepreg obtained in step 5 neatly, place it in the middle of the mold, and put it into the hot press as a whole. When the viscosity of the glue is close to the gel state, increase the temperature in stages for 4 times, and maintain the pressure for the same period of time under the same pressure, wherein the hot pressing temperature is 200-300°C and the hot pressing pressure is 0-20MPa; after curing is completed and naturally cooled to room temperature, remove the mold to obtain the material used for the copper clad laminate.
[0013] Furthermore, the set temperature in step 1 and step 5 is 80°C.
[0014] Furthermore, the staged temperature increase in step 6 is specifically 4 times: first 200°C, 5MPa, and pressure maintenance for 2h; then the temperature is increased to 220°C, 5MPa, and pressure maintenance for 2h; 240°C, 5MPa, and pressure maintenance for 2h; and finally the temperature is increased to 260°C, 5MPa, and pressure maintenance for 2h.
[0015] Furthermore, the preparation method of the cyano-containing benzoxazine is as follows: 1 mol of bisphenol A, 2 mol of polyformaldehyde, 2 mol of 4-(4-aminophenoxy)phthalonitrile and a solvent are sequentially added into a container and mixed evenly, and the temperature is raised to 85° C. and heated for reaction for 4 hours to obtain a product that is a uniform brown viscous liquid with no solid deposition at the bottom of the container; after the reaction is completed, the product is poured into water for precipitation, and then washed with 1N NaOH aqueous solution and water for 3 times respectively to obtain the target product; wherein the solvent is one or two of DMF, toluene, dioxane, xylene, and chloroform, and the solid-liquid mass ratio is 20-70%.
[0016] Further, the hyperbranched polysiloxane is prepared by the following steps:
[0017] Step A1: 15 mmol of ethyl orthosilicate, 0.1 mol of trimethyloxyphenylsilane and 8 mmol of 3-aminopropylmethyldiethoxysilane were added to a container filled with tetrahydrofuran, and the reaction mixture was cooled to 0° C. in an ice bath;
[0018] Step A2: add deionized water dropwise under vigorous stirring for 1 hour;
[0019] Step A3: The reaction mixture was stirred at 0°C for 1 hour and then at 50°C for another 2 hours;
[0020] Step A4: After rotary evaporation under reduced pressure at 55 degrees Celsius for 5-8 hours, a white powder product is obtained;
[0021] Step A5: Collect the crude product, dissolve it in CH2Cl2, and then add cold ethanol to precipitate; repeat this process at least 3 times;
[0022] Step A6: The resulting product was collected by suction filtration, volatiles were removed, and dried in a vacuum oven at room temperature for at least 48 hours to obtain a white powder product.
[0023] Compared with the existing bismaleimide resin, the present invention has the following technical effects:
[0024] 1. Increase the glass transition temperature of the resin through simple blending and copolymerization reactions.
[0025] 2. The branched structure of hyperbranched polysiloxane can be used to improve the brittleness of bismaleimide resin. The introduction of hyperbranched structure into bismaleimide resin can significantly improve the fracture toughness of the resin without affecting its heat resistance.
[0026] 3. The amino group in the hyperbranched polysiloxane can promote the ring-opening polymerization of the benzoxazine ring and the curing polymerization of the cyanide group, and can also react with the bismaleimide resin. The prepared copper-clad laminate based on the modified bismaleimide resin has excellent comprehensive performance.
[0027] In summary, the preparation method provided by the present invention has a simple process and is easy to scale up. The specific technical effects obtained are described in the examples in combination with the specific steps. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Schematic diagram of the synthesis process of benzoxazine containing cyano group (BA-Ph);
[0029] Figure 2 A schematic diagram of a preparation process provided by an embodiment of the present invention;
[0030] Figure 3 The molecular structure diagram of BMI-70;
[0031] Figure 4 The molecular structure diagram of BMI-80; DETAILED DESCRIPTION
[0032] In order to better understand the purpose, structure and function of the present invention, the following is a further detailed description of a high temperature resistant copper clad laminate based on modified bismaleimide resin and a preparation method of the present invention in conjunction with the accompanying drawings.
[0033] The invention provides a simple preparation method of a high-temperature resistant and low-expansion copper-clad laminate based on a modified bismaleimide resin. The modified bismaleimide resin obtained by the preparation method has excellent mechanical properties and heat resistance, reduces dielectric constant and dielectric loss, and improves adhesion to fibers, so as to meet the use requirements of the resin matrix of the high-performance copper-clad laminate.
[0034] Preparation method of high temperature resistant copper clad laminate based on modified bismaleimide resin Figure 2 As shown, the following steps are included:
[0035] Step 1: Add bismaleimide, homemade cyano-containing benzoxazine (BA-Ph), hyperbranched polysiloxane and solvent N,N-dimethylformamide (DMF) into a three-necked flask with a condenser and a stirrer, heat to 80°C, and stir until the solution is uniform and transparent. Specifically, the solvent may also include one or more of N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, and dioxane; the amount of BA-Ph is 5-40% of the mass of bismaleimide, the amount of hyperbranched polysiloxane is 5-20% of the mass of bismaleimide, and the mass ratio of the total mass of the three solids to the solvent liquid is 15-70%.
[0036] Step 2: The transparent solution obtained in step 1 is reacted at 120° C. for 3 h to obtain a glue solution.
[0037] Step 3: Apply the glue prepared in step 2 evenly on a 10cm*10cm glass fiber cloth, and hang the fiber cloth to drip out the excess glue. The mass ratio of glue to glass fiber cloth is 40:60. The surface coating treatment of the reinforcing fiber improves the bonding strength between the base material and the reinforcing fiber.
[0038] Step 4: Repeat the process in step 3 to obtain 8 pieces of fiberglass cloth soaked with glue.
[0039] Step 5: Put the 8 pieces of glass fiber cloth soaked with glue obtained in step 4 into an oven, set the temperature to 80°C, and dry the solvent at low temperature to obtain 8 pieces of prepreg.
[0040] Step 6: stack the prepreg obtained in step 5 neatly, sandwich it with two aluminum sheets, put it between two iron plates, and put it into the hot press as a whole. When the viscosity of the glue is close to the gel state, hold the pressure at 200℃, 5MPa for 2h, then heat it up to 220℃, 5MPa, hold the pressure for 2h, 240℃, 5MPa, hold the pressure for 2h, and finally heat it up to 260℃, 5MPa, hold the pressure for 2h. After curing is completed and naturally cooled to room temperature, remove the mold to obtain the material used for the copper clad laminate.
[0041] The resin matrix used in this copper clad laminate is made through a one-time hot pressing process, which simplifies the processing process. The resin matrix exhibits advantages such as excellent high temperature resistance, low dielectric constant, high mechanical strength and modulus.
[0042] Further, the synthesis process of cyano-containing benzoxazine (BA-Ph) is as follows Figure 1 As shown, a one-pot method is used to synthesize a phthalonitrile resin containing a benzoxazine group. Specifically, in this embodiment, 22.83g of bisphenol A, 47.05g of 4-(4-aminophenoxy)phthalonitrile (4-APN), 6.00g of polyformaldehyde, and 30ml of toluene and 30ml of dioxane as solvents are added to a three-necked flask in sequence and mixed evenly, and the temperature is raised to 85°C and heated for 4h to obtain a uniform brown viscous liquid product. Normally, there is no solid deposition at the bottom of the bottle. After the reaction is completed, pour it into water for precipitation, and then wash it with 1N NaOH aqueous solution and water for 3 times respectively to obtain BA-Ph.
[0043] The introduction of benzoxazine resin containing cyano groups can increase the degree of cross-linking reaction, thereby improving the heat resistance of the material. In addition, the hydroxyl and cyano groups in the open-ring benzoxazine, as polar groups, can effectively improve the bonding ability with the fiber.
[0044] Further, the hyperbranched polysiloxane was prepared by the following steps: 15 mmol (3.1250 g) of tetraethyl orthosilicate (TEOS), 0.1 mol (19.8290 g) of trimethyloxyphenylsilane (PTMS) and 8 mmol (1.5308 g) of 3-aminopropylmethyldiethoxysilane (APDES) were added to a 100 mL round-bottom flask containing 30 g of THF (tetrahydrofuran). The reaction mixture was cooled to 0°C in an ice bath, and 5.64 g of deionized water was added dropwise through a syringe under vigorous stirring for 1 hour. The reaction mixture was stirred at 0°C for 1 hour and then stirred at 50°C for another 2 hours. A white powdery crude product was obtained by rotary evaporation under reduced pressure. The crude product was collected, dissolved in dichloromethane (60 mL), and then precipitated by adding cold ethanol (200 mL). The typical dissolution-precipitation process was repeated at least three times, and the product was finally collected by filtration, volatiles were removed, and dried in a vacuum oven at room temperature for at least 48 hours to obtain a white powder product.
[0045] The amino groups in hyperbranched polysiloxane can promote the ring-opening polymerization of benzoxazine rings and the curing polymerization of cyano groups, and can also react with bismaleimide resins. The branched structure of hyperbranched polysiloxane can improve the brittleness of the resin. The introduction of hyperbranched structure into bismaleimide resin can significantly improve the fracture toughness of the resin without affecting its glass transition temperature.
[0046] Example 1
[0047] This embodiment provides a method for preparing a high temperature resistant copper clad laminate based on a modified bismaleimide resin, comprising the following steps:
[0048] Step 1: 30 g BDM, 3 g BA-Ph, 1.5 g hyperbranched polysiloxane, and 31.8 g N,N-dimethylformamide were added sequentially into a three-necked flask with a stirring rod and a condenser, and dissolved in an oil bath at 80° C. to obtain a clear and transparent solution;
[0049] Step 2: The transparent solution obtained in step 1 is reacted at 120° C. for 3 h to obtain a glue solution.
[0050] Step 3: Mix 32g of the glue prepared in step 2 with 8 sheets of glass fiber cloth (24g). The mass ratio of glue to glass fiber cloth is 40:60. Apply the glue evenly on each 10cm*10cm glass fiber cloth and hang the fiber cloth to drip out the excess glue.
[0051] Step 4: Put the 8 pieces of glass fiber cloth soaked with glue obtained in step 3 into a programmed oven, set the temperature to 80°C, treat the solvent, and obtain 8 pieces of prepreg.
[0052] Step 5: Stack the prepreg obtained in step 4 neatly, sandwich it with two aluminum sheets, and then put it between two iron plates. Put the whole into the hot press. When the viscosity of the glue is close to the gel state, keep the pressure at 200℃, 5MPa for 2h, then raise the temperature to 220℃, 5MPa, keep the pressure for 2h, 240℃, 5MPa, keep the pressure for 2h, and finally raise the temperature to 260℃, 5MPa, and keep the pressure for 2h.
[0053] Step 6: After step 5 is cured and naturally cooled to room temperature, the mold is removed to obtain the copper clad laminate material.
[0054] The surface of the copper clad laminate material obtained after curing is smooth without defects such as bubbles; the tested bending strength is 520MPa, the bending modulus is 32.0GPa, and the thermal decomposition temperature (T 5% ) is 377℃, and the glass transition temperature (T g ) is 273℃, the dielectric constant is 4.52 at 1MHz frequency under room temperature, and the dielectric loss is 0.0143. All data meet the standard requirements of resin for copper clad laminates.
[0055] Example 2
[0056] Step 1: Add 30g BDM, 3g BA-Ph, 3g hyperbranched polysiloxane, and 31.8g N,N-dimethylformamide into a three-necked flask with a stirring rod and a condenser. Dissolve in an oil bath at 80°C until a clear and transparent solution is obtained;
[0057] Step 2: React the transparent solution in step 1 at 120°C for 3 hours to obtain a glue solution.
[0058] Step 3: Mix 32g of the glue prepared in step 2 with 8 sheets of glass fiber cloth (24g). The mass ratio of glue to glass fiber cloth is 40:60. Apply the glue evenly on each 10cm*10cm glass fiber cloth and hang the fiber cloth to drip out the excess glue.
[0059] Step 4: Put the 8 pieces of glass fiber cloth soaked with glue obtained in step 3 into a programmed oven to process the solvent to obtain 8 pieces of prepreg.
[0060] Step 5: Stack the prepreg obtained in step 4 neatly, sandwich it with two aluminum sheets, and then put it between two iron plates. Put the whole into the hot press. When the viscosity of the glue is close to the gel state, keep the pressure at 200℃, 5MPa for 2h, then raise the temperature to 220℃, 5MPa, keep the pressure for 2h, 240℃, 5MPa, keep the pressure for 2h, and finally raise the temperature to 260℃, 5MPa, and keep the pressure for 2h.
[0061] Step 6: After step 5 is cured and naturally cooled to room temperature, the mold is removed to obtain the copper clad laminate material.
[0062] The surface of the copper clad laminate material obtained after curing is smooth without defects such as bubbles; the tested bending strength is 618MPa, the bending modulus is 34.8GPa, and the thermal decomposition temperature (T 5% ) is 401℃, and the glass transition temperature (T g ) is 285℃, the dielectric constant is 4.38 at 1MHz frequency under room temperature, and the dielectric loss is 0.0117. All data meet the standard requirements of resin for copper clad laminates.
[0063] Example 3
[0064] Step 1: Add 30g BDM, 6g BA-Ph, 3g hyperbranched polysiloxane, and 31.8g N,N-dimethylformamide into a three-necked flask with a stirring rod and a condenser. Dissolve in an oil bath at 80°C until a clear and transparent solution is obtained;
[0065] Step 2: React the transparent solution in step 1 at 120°C for 3 hours to obtain a glue solution.
[0066] Step 3: Mix 32g of the glue prepared in step 2 with 8 sheets of glass fiber cloth (24g). The mass ratio of glue to glass fiber cloth is 40:60. Apply the glue evenly on each 10cm*10cm glass fiber cloth and hang the fiber cloth to drip out the excess glue.
[0067] Step 4: Put the 8 pieces of glass fiber cloth soaked with glue obtained in step 3 into a programmed oven to process the solvent to obtain 8 pieces of prepreg.
[0068] Step 5: Stack the prepreg obtained in step 4 neatly, sandwich it with two aluminum sheets, and then put it between two iron plates. Put the whole into the hot press. When the viscosity of the glue is close to the gel state, keep the pressure at 200℃, 5MPa for 2h, then raise the temperature to 220℃, 5MPa, keep the pressure for 2h, 240℃, 5MPa, keep the pressure for 2h, and finally raise the temperature to 260℃, 5MPa, and keep the pressure for 2h.
[0069] Step 6: After step 5 is cured and naturally cooled to room temperature, the mold is removed to obtain the copper clad laminate material.
[0070] The surface of the copper clad laminate material obtained after curing is smooth without defects such as bubbles; the tested bending strength is 656MPa, the bending modulus is 36.2GPa, and the thermal decomposition temperature (T 5% ) is 415℃, and the glass transition temperature (T g ) is 302℃, the dielectric constant is 4.57 at 1MHz frequency under room temperature, and the dielectric loss is 0.0135. All data meet the standard requirements of resin for copper clad laminates.
[0071] Example 4
[0072] Step 1: Add 30g BDM, 9g BA-Ph, 3g hyperbranched polysiloxane, and 31.8g N,N-dimethylformamide into a three-necked flask with a stirring rod and a condenser. Dissolve in an oil bath at 80°C until a clear and transparent solution is obtained;
[0073] Step 2: React the transparent solution in step 1 at 120°C for 3 hours to obtain a glue solution.
[0074] Step 3: Add 32g of the glue prepared in step 2 and 24g of 8 pieces of glass fiber cloth, with the mass ratio of solution to glass fiber cloth being 40:60. Apply the glue evenly on each 10cm*10cm glass fiber cloth, and hang the fiber cloth to drip out the excess glue.
[0075] Step 4: Put the 8 pieces of glass fiber cloth soaked with glue obtained in step 3 into a programmed oven to process the solvent to obtain 8 pieces of prepreg.
[0076] Step 5: Stack the prepreg obtained in step 4 neatly, sandwich it with two aluminum sheets, and then put it between two iron plates. Put the whole into the hot press. When the viscosity of the glue is close to the gel state, keep the pressure at 200℃, 5MPa for 2h, then raise the temperature to 220℃, 5MPa, keep the pressure for 2h, 240℃, 5MPa, keep the pressure for 2h, and finally raise the temperature to 260℃, 5MPa, and keep the pressure for 2h.
[0077] Step 6: After step 5 is cured and naturally cooled to room temperature, the mold is removed to obtain the copper clad laminate material.
[0078] The surface of the copper clad laminate material obtained after curing is smooth without defects such as bubbles; the tested bending strength is 582MPa, the bending modulus is 31.2GPa, and the thermal decomposition temperature (T 5% ) is 438℃, and the glass transition temperature (T g ) is 328℃, the dielectric constant is 4.74 at 1MHz frequency under room temperature, and the dielectric loss is 0.0156. All data meet the standard requirements of resin for copper clad laminates.
[0079] Example 5
[0080] Step 1: 30g BMI-70, 6g BA-Ph, 3g hyperbranched polysiloxane, and 31.8g N,N-dimethylformamide were added to a three-necked flask with a stirring rod and a condenser tube. Dissolved in an oil bath at 80°C until a clear and transparent solution was obtained; the molecular structure of BMI-70 is as follows: Figure 3 As shown;
[0081] Step 2: React the transparent solution in step 1 at 120°C for 3 hours to obtain a glue solution.
[0082] Step 3: Add 32g of the glue prepared in step 2 and 24g of 8 pieces of glass fiber cloth, with the mass ratio of solution to glass fiber cloth being 40:60. Apply the glue evenly on each 10cm*10cm glass fiber cloth, and hang the fiber cloth to drip out the excess glue.
[0083] Step 4: Put the 8 pieces of glass fiber cloth soaked with glue obtained in step 3 into a programmed oven to process the solvent to obtain 8 pieces of prepreg.
[0084] Step 5: Stack the prepreg obtained in step 4 neatly, sandwich it with two aluminum sheets, and then put it between two iron plates. Put the whole into the hot press. When the viscosity of the glue is close to the gel state, keep the pressure at 200℃, 5MPa for 2h, then raise the temperature to 220℃, 5MPa, keep the pressure for 2h, 240℃, 5MPa, keep the pressure for 2h, and finally raise the temperature to 260℃, 5MPa, and keep the pressure for 2h.
[0085] Step 6: After step 5 is cured and naturally cooled to room temperature, the mold is removed to obtain the copper clad laminate material.
[0086] The surface of the copper clad laminate material obtained after curing is smooth without defects such as bubbles; the tested bending strength is 635MPa, the bending modulus is 33.2GPa, and the thermal decomposition temperature (T 5% ) is 388℃, and the glass transition temperature (T g ) is 296℃, the dielectric constant is 4.35 at 1MHz frequency under room temperature, and the dielectric loss is 0.0106. All data meet the standard requirements for resins for copper clad laminates.
[0087] Example 6
[0088] Step 1: 30g BMI-80, 6g BA-Ph, 3g hyperbranched polysiloxane, and 31.8g N,N-dimethylformamide were added to a three-necked flask with a stirring rod and a condenser tube. Dissolved in an oil bath at 80°C until a clear and transparent solution was obtained; the molecular structure of BMI-80 is as follows: Figure 4 As shown;
[0089] Step 2: React the transparent solution in step 1 at 120°C for 3 hours to obtain a glue solution.
[0090] Step 3: Add 32g of the glue prepared in step 2 and 24g of 8 pieces of glass fiber cloth, with the mass ratio of solution to glass fiber cloth being 40:60. Apply the glue evenly on each 10cm*10cm glass fiber cloth, and hang the fiber cloth to drip out the excess glue.
[0091] Step 4: Put the 8 pieces of glass fiber cloth soaked with glue obtained in step 3 into a programmed oven to process the solvent to obtain 8 pieces of prepreg.
[0092] Step 5: Stack the prepreg obtained in step 4 neatly, sandwich it with two aluminum sheets, and then put it between two iron plates. Put the whole into the hot press. When the viscosity of the glue is close to the gel state, keep the pressure at 200℃, 5MPa for 2h, then raise the temperature to 220℃, 5MPa, keep the pressure for 2h, 240℃, 5MPa, keep the pressure for 2h, and finally raise the temperature to 260℃, 5MPa, and keep the pressure for 2h.
[0093] Step 6: After step 5 is cured and naturally cooled to room temperature, the mold is removed to obtain the copper clad laminate material.
[0094] The surface of the copper clad laminate material obtained after curing is smooth without defects such as bubbles; the tested bending strength is 670MPa, the bending modulus is 35.8GPa, and the thermal decomposition temperature (T 5% ) is 427℃, and the glass transition temperature (T g ) is 308℃, the dielectric constant is 4.62 at 1MHz frequency under room temperature, and the dielectric loss is 0.0124. All data meet the standard requirements of resin for copper clad laminates.
[0095] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.
Claims
1. A method for preparing a high temperature resistant copper clad laminate based on modified bismaleimide resin, characterized in that: The following steps are involved: Step 1: Add three solids, namely, bismaleimide, cyano-containing benzoxazine BA-Ph, and hyperbranched polysiloxane, and a solvent into a reaction bottle, heat to a set temperature, and stir until the solution is uniform and transparent; Step 2: react the transparent solution obtained in step 1 at 120° C. for 3 hours to obtain a glue solution; Step 3: Apply the glue prepared in step 2 evenly on the glass fiber cloth, and hang the fiber cloth to drip out the excess glue; Step 4: Repeat the process of step 3 to obtain 8 pieces of glass fiber cloth soaked with glue; Step 5: Put the 8 pieces of glass fiber cloth soaked with glue obtained in step 4 into an oven to dry the solvent at a set temperature to obtain 8 pieces of prepreg; Step 6: stack the prepreg obtained in step 5 neatly, place it in the middle of the mold, and put it into the hot press as a whole. When the viscosity of the glue is close to the gel state, heat it up four times in stages and maintain the same time period under the same pressure, wherein the hot pressing temperature is 200-300°C and the hot pressing pressure is 0-20MPa. After curing is completed and naturally cooled to room temperature, remove the mold to obtain the material used for the copper clad laminate.
2. The method for preparing a high temperature resistant copper clad laminate based on modified bismaleimide resin according to claim 1, characterized in that: In the step 1, the mass ratio of the total mass of the three solids to the mass of the solvent liquid is 15-70%, the amount of BA-Ph is 5-40% of the mass of bismaleimide, and the amount of hyperbranched polysiloxane is 5-20% of the mass of bismaleimide.
3. The method for preparing a high temperature resistant copper clad laminate based on modified bismaleimide resin according to claim 2, characterized in that: The solvent in step 1 includes one or more of N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, N,N-dimethylacetamide, and xylene.
4. The method for preparing a high temperature resistant copper clad laminate based on modified bismaleimide resin according to claim 3, characterized in that: The set temperature in the step 1 and the step 5 is 80°C.
5. The method for preparing a high temperature resistant copper clad laminate based on modified bismaleimide resin according to claim 4, characterized in that: The staged temperature increase in step 6 is specifically 4 times: first 200°C, 5MPa, and pressure maintenance for 2h; then the temperature is increased to 220°C, 5MPa, and pressure maintenance for 2h; 240°C, 5MPa, and pressure maintenance for 2h; and finally the temperature is increased to 260°C, 5MPa, and pressure maintenance for 2h.
6. The method for preparing a high temperature resistant copper clad laminate based on modified bismaleimide resin according to claim 5, characterized in that: The preparation method of the cyano-containing benzoxazine BA-Ph is as follows: 1 mol of bisphenol A, 2 mol of polyformaldehyde, 2 mol of 4-(4-aminophenoxy)phthalonitrile and a solvent are sequentially added into a container and mixed evenly, and the temperature is raised to 85° C. and heated for reaction for 4 hours to obtain a product that is a uniform brown viscous liquid with no solid deposition at the bottom of the container; after the reaction is completed, the product is poured into water for precipitation, and then washed with 1N NaOH aqueous solution and water for 3 times respectively to obtain the target product; The solvent is one or two of DMF, toluene, dioxane, xylene and chloroform, and the solid-liquid mass ratio is 20-70%.
7. The method for preparing a high temperature resistant copper clad laminate based on modified bismaleimide resin according to claim 6, characterized in that: The hyperbranched polysiloxane is prepared by the following steps: Step A1: 15 mmol of ethyl orthosilicate, 0.1 mol of trimethyloxyphenylsilane and 8 mmol of 3-aminopropylmethyldiethoxysilane were added to a reaction bottle containing tetrahydrofuran, and the reaction mixture was cooled to 0° C. in an ice bath; Step A2: add deionized water dropwise under vigorous stirring for 1 hour; Step A3: The reaction mixture was stirred at 0°C for 1 hour and then at 50°C for another 2 hours; Step A4: Rotary evaporation under reduced pressure can obtain a crude white powder product; Step A5: collecting the crude product, dissolving the crude product in dichloromethane, and then adding cold ethanol for precipitation; repeating this process at least 3 times; Step A6: The product was collected by filtration, volatiles were removed and dried in a vacuum oven at room temperature for at least 48 hours to obtain a white powder product.
8. A high temperature resistant copper clad laminate based on modified bismaleimide resin, characterized in that: The material used for the high temperature resistant copper clad laminate is made based on the preparation method described in any one of claims 1-7.
Citation Information
Patent Citations
Resin composition and prepreg laminated board manufactured by employing same
CN104830059A
Resin composition and product thereof
CN116333225A
Phenolphthalein polyarylene ether nitrile modified bismaleimide-triazine resin and preparation method of glass fiber reinforced composite material of phenolphthalein polyarylene ether nitrile modified bismaleimide-triazine resin
CN118994905A
Modified polyimide resin composition and manufacturing method therefor, and prepreg and laminate using the same
JP2017101152A
Di-cinnamyl compounds and methods for use thereof
US20090288768A1